2017
DOI: 10.2147/ijwh.s145191
|View full text |Cite
|
Sign up to set email alerts
|

Effect of age and estrogen on biochemical markers of bone turnover in postmenopausal women: a population-based study from Nepal

Abstract: BackgroundOsteoporosis, a common disease worldwide, is characterized by low bone mass and architectural deterioration of bone tissue, leading to enhanced bone fragility and increase in fracture risks. Both menopause and aging are related factors leading to greater risk of bone disease, particularly among postmenopausal women. Hence, the main purpose of this study was to investigate the differences in biochemical markers of bone turnover and to evaluate the association of hormones and age-related factors with b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
27
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 21 publications
11
27
1
1
Order By: Relevance
“…In the present study also, there is no significant correlation observed. 2,3,6,7 In our study also there is a significant correlation found with a P-value of 0.019. This difference may be due to the changes in dietary intake of phosphorus and ethinicity.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…In the present study also, there is no significant correlation observed. 2,3,6,7 In our study also there is a significant correlation found with a P-value of 0.019. This difference may be due to the changes in dietary intake of phosphorus and ethinicity.…”
Section: Discussionsupporting
confidence: 75%
“…6,7 Bone formation outpaces resorption until peak bone mass is reached at around 30 years of age. 2 Once the women is in her fourth decade, there is a gradual loss of bone mineral density. 8 According to literature it was found that from the first year after menopause there is a progressive fall in bone density values up to 5 years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We next asked whether there is an age-dependent effect of estrogen on callus BMD as measured by pQCT because of the reduced sensitivity to estrogen with age [22]. Figure 4 summarizes the data from CALCBD ( g. 4a1 and 4b1) and the CORTBD analyses ( g. 4a2 and 4b2) of the healthy ( g. 4a1 and a2) and fractured ( g. 4b1 and b2) arm of postmenopausal women of different ages.…”
Section: Calculated Bone Density and Cortical Bone Density In Estrogementioning
confidence: 99%